Valores científicos e florescimento humano - Fonseca, Bruno Lima da (2013)
The study has the interest to investigate the existing values in science and analyze the possibility of promotion of ethics in the scientific pratices in the contemporaneity. The basis for this analysis is on Hugh Lacey s studies on the search for an epistemological model based on the adequacy of present values in scientific practices to social projection and human needs. This analysis shows that to have a better understanding of science and its objective, we should distinguish the values, the moments and the decisive strategies for the development of science. The Lacey s proposed has two articulations a distinction of values (cognitive and noncognitive) and a distinguish of the proper times of scientific practice that would enable a better explanation and justification of the problem of ―value-free science‖. To Lacey, there are three moments of scientific activity that allow us to analyse the performance of values: the moment M1, to adopt ways and strategies for research; the moment M2, to accept theories; and the moment M3, to apply scientific knowledge. The distinction of values is needed to support the view that scientific knowledge can be impartial and still serve as social values. Already, the distinction of moments of scientific activity allows the author to indicate the suitable place for investigating social influences in the research (at the moments M1 and M3). We realize that the modern tradition of science used a materialist understanding that selected restricted and one-dimensional strategies of research, overly linked to noncongnitive values of control of natural objects that privilege capitalists values, that, almost always, do not guarantee the enjoyment of other values essential for the human welfare. Therefore, this discussion suggests the importance of rethink the present values in science for a scientific activity that balances the ideal of the understanding of the world, together with the ability to generate useful Technologies for the flourishing of humanity.